If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3x + -2 = -9 + -4x Reorder the terms: -2 + -3x = -9 + -4x Solving -2 + -3x = -9 + -4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4x' to each side of the equation. -2 + -3x + 4x = -9 + -4x + 4x Combine like terms: -3x + 4x = 1x -2 + 1x = -9 + -4x + 4x Combine like terms: -4x + 4x = 0 -2 + 1x = -9 + 0 -2 + 1x = -9 Add '2' to each side of the equation. -2 + 2 + 1x = -9 + 2 Combine like terms: -2 + 2 = 0 0 + 1x = -9 + 2 1x = -9 + 2 Combine like terms: -9 + 2 = -7 1x = -7 Divide each side by '1'. x = -7 Simplifying x = -7
| X^2-9x+0=0 | | 5x+88=9y | | 64-3x=7x+2 | | j*(-66)=198 | | 3x+11=95-5x | | 9(8c-1)-16=70c+9 | | -5v-8(1+7n)=-8 | | 3a-11=a+15 | | x+100=500 | | 4+4x=48 | | c*(-19-(-27))=-160 | | x+x-3005=7815 | | -27-r=9 | | j*(-6)=330 | | j*(-6)=339 | | k+(-14)=-40 | | .13x+14.95=.39x-15 | | -7*n=175 | | -7*=175 | | 18955=8x+75 | | 6x+29=3x+71 | | x^9y^6/x^-3y^2 | | x^9y^6/x^-3y^2 | | -2*k=182 | | X^2+5x+0=0 | | -6-g=31 | | S/(-29)=-22 | | -40*c=560 | | -40*=560 | | 5x+1=180 | | -8+k=-11 | | -59-u=-26 |